Does the Factor Structure of IQ Differ Between the Differential Ability Scales (DAS‐II) Normative Sample and Autistic Children?. Issue 7 (29th February 2020) - Clements, Caitlin C.; Watkins, Marley W.; Schultz, Robert T.; Yerys, Benjamin E.
Abstract : The Differential Abilities Scales, 2nd edition (DAS‐II) is frequently used to assess intelligence in autism spectrum disorder (ASD). However, it remains unknown whether the DAS‐II measurement model (e.g., factor structure, loadings), which was developed on a normative sample, holds for the autistic population or requires alternative score interpretations. We obtained DAS‐II data from 1, 316 autistic individuals in the Simons Simplex Consortium and 2, 400 individuals in the normative data set. We combined ASD and normative data sets for multigroup confirmatory factor analyses to assess different levels of measurement invariance, or how well the same measurement model fit both data sets: "weak" or metric, "strong" or scalar, and partial scalar if full scalar was not achieved. A weak invariance model showed excellent fit (Confirmatory Fit Index [CFI] > 0.995, Tucker Lewis Index [TLI] > 0.995, root mean square error of approximation [RMSEA] < 0.025), but a strong invariance model demonstrated a significant deterioration in fit during permutation testing (all p's<0.001), suggesting measurement bias, meaning systematic error when assessing autistic children. Fit improved significantly, and partial scalar invariance was achieved when either of the two spatial subtest (Recall of Designs or Pattern Construction) intercepts was permitted to vary between the ASD and normative groups, pinpointing these subtests as the source of bias. The DAS‐II appears to measure verbal and nonverbal—but not spatial—intelligence in autistic children similarly as in normative sample children. These results may be driven by Pattern Construction, which shows higher scores than other subtests in the ASD sample. Clinicians assessing autistic children with the DAS‐II should interpret verbal and nonverbal reasoning composite scores over the spatial score or General Composite Ability. Autism Res 2020, 13 : 1184‐1194. © 2020 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: The Differential Abilities Scales, 2nd edition (DAS‐II) is a popular intelligence quotient (IQ) test for assessing children with autism. This article shows that the DAS‐II spatial standardized scores should be interpreted with caution because they hold a different meaning for autistic children. Verbal and nonverbal reasoning scores appear valid and to hold the same meaning for those with and without autism spectrum disorder.